Réponses

2013-02-04T19:30:40+01:00

b) (x+5)² = 39+25 :

Donc x² + 10x + 25 = 39 + 25

x² + 10 x + 25 - 39 - 25 = 0

x² + 10x - 39 = 0

Donc delta = b² - 4ac = 10² - 4 * 1 * (-39) = 100 + 156 = 256

Donc x1 = (-b+racine(delta))/2a = (-10 + 16)/2 = 3

Et x2 = (-b-racine(delta))/2a = (-10 - 16) / 2 = -13

Donc tu as deux solutions :

 

x1 = 3 et x2 = -13

Voilà bisoux :)

2013-02-04T19:35:42+01:00

b) (x+5)2 = 39+25

     x2+25=39+25

     x2=39+25-25

     x2=39 

     X= racine carré de 39

environ egale a 6,2